PERAN PASUKAN PELOPOR BRIMOB POLDA SUMATERA UTARA DALAM PENANGGULANGAN AKSI TERORISME DITINJAU DARI PERSPEKTIF UNDANG-UNDANG NO. 5 TAHUN 2018 TENTANG TERORISME - Ismed Batubara, Januar Fazhari, (NERACA KEADILAN, 2025)
This research is motivated by the increasing threat of terrorism in Indonesia, which demands a high level of preparedness from all law enforcement agencies, particularly the Mobile Brigade Corps (Brimob) of the Indonesian National Police. The aim of this studyis to analyze the role of the Brimob Pioneer Unit in counter- terrorism efforts, to examine the implementation of Law Number 5 of 2018 as the legal basis for their duties, and to identify operational challenges faced in the field. This research uses a qualitative approach with a descriptive-analytical method. Data were obtained through interviews with members of the Brimob Pioneer Unit of the North Sumatra Regional Police and documentation of counter-terrorism activities, and were analyzed using juridical and theoretical approaches. The results of the study show that the Brimob Pioneer Unit plays a comprehensive and structured role in combating terrorism, including a preventive role through patrols and counter-radicalization outreach; a repressive role in securing, arresting, and evacuating civilians; and a post-incident role in recovery and support for deradicalization programs.The implementation of Law Number 5 of 2018 provides legitimacy and a legal framework that supports the execution of duties in a measured and professional manner. Challenges such as limited resources, inter-agency coordination, and psychological support for personnel remain key concerns in efforts to enhance operational effectiveness. This study recommends improvementsintacticalandmentaltraining,as well as strengthening inter-agency synergy as part of a sustainable strategy to maintain national security.